Association of circulating cholesteryl ester transfer protein activity with incidence of cardiovascular disease in the community - Vasan, Ramachandran S. (2009)
BACKGROUND: Plasma high-density lipoprotein cholesterol (HDL-C) concentration is inversely related to the risk of cardiovascular disease (CVD). Inhibiting cholesteryl ester transfer protein (CETP) activity raises HDL-C and may be cardioprotective, but an initial clinical trial with a CETP inhibitor was prematurely stopped due to increased CVD in treated patients, raising concerns about this approach. Data relating circulating CETP concentrations to CVD incidence in the community are conflicting. METHODS AND RESULTS: Plasma CETP activity was measured in 1978 Framingham Study participants (mean age 51 years, 54% women) who attended a routine examination in 1987–90 and were free of CVD. On follow-up (mean 15.1 years), 320 participants experienced a first CVD event (fatal or non-fatal coronary heart disease, cerebrovascular disease, peripheral vascular disease, or heart failure). In multivariable analyses adjusting for standard risk factors including HDL-C, plasma CETP activity was inversely related to the incidence of CVD events (hazards ratio [HR] for activity ≥median 0.72, 95% CI 0.57–0.90, p=0.004 [compared to <median]; HR per SD increment, 0.86, 95% CI 0.76–0.97, p=0.01). The inverse association of CETP activity with CVD incidence remained robust in time-dependent models updating standard risk factors every 4 years, and was maintained in analyses of incident ‘hard’ CVD events (myocardial infarction, stroke or heart failure). CONCLUSIONS: In our prospective investigation of a community-based sample, lower plasma CETP activity was associated with greater CVD risk. These observations, if confirmed, challenge the concept that CETP inhibition may lower CVD risk.